2014
DOI: 10.1073/pnas.1402911111
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome activation causes dual recruitment of NLRC4 and NLRP3 to the same macromolecular complex

Abstract: Pathogen recognition by nucleotide-binding oligomerization domain-like receptor (NLR) results in the formation of a macromolecular protein complex (inflammasome) that drives protective inflammatory responses in the host. It is thought that the number of inflammasome complexes forming in a cell is determined by the number of NLRs being activated, with each NLR initiating its own inflammasome assembly independent of one another; however, we show here that the important foodborne pathogen Salmonella enterica sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
322
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(362 citation statements)
references
References 37 publications
27
322
0
13
Order By: Relevance
“…Experiments were next performed to determine whether the regulation of caspase-8 was downstream of the Nlrp3 inflammasome. The activation of the Nlrp3 inflammasome using the canonical agonist nigericin in bone marrow-derived macrophages (BMDM) results in the activation of both caspase-1 and caspase-8 as previously reported 4,13 (Supplementary Figure S5). In the absence of caspase-1 or caspase-11, caspase-8 activation by nigericin is maintained confirming that caspase-8 is a downstream effector of the Nlrp3 inflammasome.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Experiments were next performed to determine whether the regulation of caspase-8 was downstream of the Nlrp3 inflammasome. The activation of the Nlrp3 inflammasome using the canonical agonist nigericin in bone marrow-derived macrophages (BMDM) results in the activation of both caspase-1 and caspase-8 as previously reported 4,13 (Supplementary Figure S5). In the absence of caspase-1 or caspase-11, caspase-8 activation by nigericin is maintained confirming that caspase-8 is a downstream effector of the Nlrp3 inflammasome.…”
Section: Resultssupporting
confidence: 72%
“…6,10 Initiation of mitochondrial apoptosis also releases SMAC/DIABLO, which inhibits XIAP and enables caspase-3 to further activate caspase-8. 11 Caspase-8 is also activated downstream of the NLRP3, AIM2 and NLRC4 inflammasomes in response to canonical triggers in macrophages 4,[12][13][14] or downstream of Dectin-1 in dendritic cells. [15][16][17] The activation of caspase-8 in leukocytes requires ASC and regulates the non-canonical maturation of IL-1β.…”
mentioning
confidence: 99%
“…Super-resolution fluorescence microscopy revealed that caspase-1 makes the core, surrounded by NLRP3 and NLRC4 rings, while ASC positions into a large external ring. Colocalization of NLRP3 and NLRC4 was only partial, with NLRP3 composing a ring with lower diameter than NLRC4 [64]. Interestingly, while hypoosmotic conditions activate the NLRP3 inflammasome due to K + efflux and Ca 2+ influx [65], hyperosmotic conditions signal through NLRP3 and NLRC4, independently of K + efflux (Fig.…”
Section: The Role Of Asc In Cytokine Maturation and Pyroptosismentioning
confidence: 88%
“…NLRC4 is able to co-immunoprecipitate with NLRP3 [63] and there are more indications that various NLRs can be found in the same complex. Both receptors were recruited to the same macromolecular complex upon S. Typhimurium infection [64]. Super-resolution fluorescence microscopy revealed that caspase-1 makes the core, surrounded by NLRP3 and NLRC4 rings, while ASC positions into a large external ring.…”
Section: The Role Of Asc In Cytokine Maturation and Pyroptosismentioning
confidence: 99%
“…To catalyze the proteolytic cleavage of pro-interleukin (IL)-1β and pro-IL-18, which results into pyroptosis, NLRs and ALRs engage caspase-1, through the adapter protein apoptosis-associated specklike protein, containing a CARD (ASC), (Man and Kanneganti, 2015). To become activated AIM2 or NLRP3 require the polymerization of the N terminal pyridine domain (PYD) of ASC (Lu et al, 2014;Cai et al, 2014), which, as final step, leads to the formation of a single and distinct inflammasome speck that could be detected in primary macrophages and dendritic cells (DCs) (Man et al, 2014;2015a;Belhocine and Monack, 2012). Recently Bakele and colleagues showed that human neutrophils also express the key components of the NLRP3 and AIM2 inflammasome machinery in different intra-cellular compartments and they are capable to release key cytokines.…”
Section: Introductionmentioning
confidence: 99%